LGBTQI+ Experiences of HIV Management Services at Primary Healthcare Facilities in Gauteng Province, South Africa - Desirée Morakane Mulemfo; Idah Moyo; Azwihangwisi Helen Mavhandu-Mudzusi (Advances in Public Health)
Lesbian, gay, bisexual, transgender, queer, intersex, and plus (LGBTQI+) people are still discriminated against in South Africa, irrespective of their protection by the constitution of South Africa. The study explores the experiences of LGBTQI+ people when accessing HIV management services at public primary healthcare (PHC) facilities in Gauteng Province. Interpretive phenomenological analysis (IPA) was used. Data were collected through in-depth face-to-face interviews with six individuals who self-identified as LGBTQI+. The interviews were audio recorded with the permission of the participants. The data were transcribed verbatim and analyzed using the IPA framework. The findings indicate that LGBTQI+ people are marginalized, discriminated against, and stigmatized in the public PHC system, exposing them to unequal access to healthcare services. The heterocentric system disadvantages them from accessing specific HIV management services and appropriate preventive commodities. The study concludes that gender diversity, inclusion and sensitivity in healthcare provision, and specific LGBTQI+ training for healthcare providers, are crucial components of ensuring LGBTQI+ people’s access to quality HIV management services.